Atomic‐Level Insight into Optimizing the Hydrogen Evolution Pathway over a Co1‐N4 Single‐Site Photocatalyst. (28th August 2017) - Cao, Yuanjie; Chen, Si; Luo, Qiquan; Yan, Huan; Lin, Yue; Liu, Wei; Cao, Linlin; Lu, Junling; Yang, Jinlong; Yao, Tao; Wei, Shiqiang
Abstract: Knowledge of the photocatalytic H2 evolution mechanism is of great importance for designing active catalysts toward a sustainable energy supply. An atomic‐level insight, design, and fabrication of single‐site Co1 ‐N4 composite as a prototypical photocatalyst for efficient H2 production is reported. Correlated atomic characterizations verify that atomically dispersed Co atoms are successfully grafted by covalently forming a Co1 ‐N4 structure on g‐C3 N4 nanosheets by atomic layer deposition. Different from the conventional homolytic or heterolytic pathway, theoretical investigations reveal that the coordinated donor nitrogen increases the electron density and lowers the formation barrier of key Co hydride intermediate, thereby accelerating H–H coupling to facilitate H2 generation. As a result, the composite photocatalyst exhibits a robust H2 production activity up to 10.8 μmol h −1, 11 times higher than that of pristine counterpart.